2003
DOI: 10.1128/iai.71.10.6088-6094.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a New Staphylococcal Enterotoxin-Related Putative Toxin Encoded by Two Kinds of Plasmids

Abstract: We identified and characterized a novel staphylococcal enterotoxin-like putative toxin, which is named SER. Nucleotide sequencing analysis of the ser gene revealed that ser was most closely related to the seg gene. The ser gene product, SER, was successfully expressed as a recombinant protein in an Escherichia coli expression system, and recombinant SER (rSER) showed significant T-cell stimulation activity. The SER production in ser-harboring Staphylococcus aureus strains was confirmed by Western blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
138
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 31 publications
6
138
0
4
Order By: Relevance
“…The fourth classical enterotoxin gene, named sed, was detected in 2 (1.4%) pus agr group II isolates, in both cases, this virulence gene was accompanied by ser gene, with selm and selo. It was reported that the coexistence of sed, selj and ser genes are commonly found on plasmid pIB485 [51,52]. However, ser gene was also found in two other agr group III S.aureus isolates (isolated from pus and urinary tract infections), without carrying the sed gene.…”
Section: Discussionmentioning
confidence: 98%
“…The fourth classical enterotoxin gene, named sed, was detected in 2 (1.4%) pus agr group II isolates, in both cases, this virulence gene was accompanied by ser gene, with selm and selo. It was reported that the coexistence of sed, selj and ser genes are commonly found on plasmid pIB485 [51,52]. However, ser gene was also found in two other agr group III S.aureus isolates (isolated from pus and urinary tract infections), without carrying the sed gene.…”
Section: Discussionmentioning
confidence: 98%
“…aureus isolates from subclinical mastitis and kareish cheese. Multiplex PCR for 10 S. aureus isolates (1-4 isolated from subclinical mastitis; 5-10 from kareish cheese), the sea genes were positive in 6 samples (2, 3, 5, 6, 7 and 10) at 102 bp ; the seb genes detected in 5 samples (1,3,7,8,9) at 164 bp; the see detected in 6 samples (2,3,5,6,7,10) at 209 bp, with no detection for sec and sed genes at 451 bp and 278 bp respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus assured via consumption of contaminated food products and milk products by S. aureus toxins [7]. In generally, early study of [8] reported that 14% to 40% of all human food poisoning outbreaks were associated with staphylococcal enterotoxins, that manifested at first by sudden onset of fever, vomiting, nausea, abdominal cramps and diarrhea [9,10]. The existence of some virulence factors as enzymes, toxins, surface antigens, and capsule have an important role in S. aureus pathogenicity as in intramammary infection, it depends on the induction of immunosuppression [11] through stimulating of the proinflammatory cytokines and T-cell that evoked the inflammatory features.…”
Section: Introductionmentioning
confidence: 99%
“…The staphylococcal enterotoxins are considered superantigens, characterized by simultaneous connections to the major complex of histocompatibility class II in an antigen presenting cell and T cell receptors, without the presence of Recently, several other toxins have been described and their genes have been sequenced, known as SEK, SEL, SEM, SEN, SEO, SEP, SEQ, SER and SEU (8,11,14,21,22,23). Besides SEH, SEI and SEG, which present emetic activity (17,30) …”
Section: Introductionmentioning
confidence: 99%